Prediction of NOx emissions for an RQL combustor using a stirred reactor modelling approach - Prakash, Atma (Cranfield University, 2015)
In an effort to reduce NOX emissions both in the landing and take-off (LTO) cycle as well as in cruise, significant research has been conducted on novel aero-engine low emissions combustor design concepts. Preliminary combustor design and emissions prediction software tools are becoming increasingly important during the conceptual design phase of aero-engine combustors. They allow a large number of designs to be explored, in a relatively short amount of time, thereby identifying the most promising designs to consider for further development. There are three methods for NOX emission prediction; correlations, stirred reactor models and CFD models. Correlation methods are derived from experimental results and are therefore only applicable for combustors for which data is available. The stirred reactor modelling approach provides a reasonably good compromise with respect to computational time and robustness relative to correlation and CFD based methods. The stirred reactor method assumes finite rate chemistry inside the combustor using simplified chemical kinetic models. The basic concept of the reactor-based method is to split the combustor into a number of reactors (perfectly or partially stirred) to compute the overall emissions. The primary objective of this doctoral research was to assess the suitability and limitations of the stirred reactor modelling approach to predict NOX emissions of a Rich-Burn Quick-Quench and Lean-Burn (RQL) combustor concept. The geometry of the RQL combustor and the model constraints were assumed from a NASA test rig experiment. The stirred reactor emission prediction model developed was verified using this test data. The results suggest that, based on the modelling assumptions made, the stirred reactor modelling approach is able to capture the trends of emissions (with changing boundary conditions) even though there are discrepancies in the absolute values. This suggests that the stirred reactor model is a useful tool during the preliminary design phase to quantify the impact of changes in boundary conditions/design parameters on changes in NOX emissions ... [cont.].
Keywords: NOX; CO; Combustor; Emission Prediction; Novel Combustor; RQL; Stirred Reactor & Shale gas